Comparative transcriptome analysis reveals different defence responses during the early stage of wounding stress in Chi-Nan germplasm and ordinary Aquilaria sinensis - Lv, Feifei; Yang, Yun; Sun, Peiwen; Zhang, Yan; Liu, Peiwei; Fan, Xiaohong; Xu, Yanhong; Wei, Jianhe (BMC plant biology, 2022)
Agarwood is a valuable Chinese medicinal herb and spice that is produced from wounded Aquilaria spp., is widely used in Southeast Asia and is highly traded on the market. The lack of highly responsive Aquilaria lines has seriously restricted agarwood yield and the development of its industry. In this article, a comparative transcriptome analysis was carried out between ordinary A. sinensis and Chi-Nan germplasm, which is a kind of A. sinensis tree with high agarwood-producing capacity in response to wounding stress, to elucidate the molecular mechanism underlying wounding stress in different A. sinensis germplasm resources and to help identify and breed high agarwood-producing strains. A total of 2427 and 1153 differentially expressed genes (DEGs) were detected in wounded ordinary A. sinensis and Chi-Nan germplasm compared with the control groups, respectively. KEGG enrichment analysis revealed that genes participating in starch metabolism, secondary metabolism and plant hormone signal transduction might play major roles in the early regulation of wound stress. 86 DEGs related to oxygen metabolism, JA pathway and sesquiterpene biosynthesis were identified. The majority of the expression of these genes was differentially induced between two germplasm resources under wounding stress. 13 candidate genes related to defence and sesquiterpene biosynthesis were obtained by WGCNA. Furthermore, the expression pattern of genes were verified by qRT-PCR. The candidate genes expression levels were higher in Chi-Nan germplasm than that in ordinary A. sinensis during early stage of wounding stress, which may play important roles in regulating high agarwood-producing capacity in Chi-Nan germplasm. Compared with A. sinensis, Chi-Nan germplasm invoked different biological processes in response to wounding stress. The genes related to defence signals and sesquiterepene biosynthesis pathway were induced to expression differentially between two germplasm resources. A total of 13 candidate genes were identified, which may correlate with high agarwood-producting capacity in Chi-Nan germplasm during the early stage of wounding stress. These genes will contribute to the development of functional molecular markers and the rapid breeding highly of responsive Aquilaria lines.